Conformational analysis of r(CGCGCG) in aqueous solution: an A-type double helical conformation studied by two-dimensional nuclear Overhauser effect spectroscopy. - Westerink, H P (1984)
The conformation of the hexanucleoside pentaphosphate r( CGCGCG ) in aqueous solution was studied by circular dichroism, 1H- and 31P-NMR spectroscopy. The base-, H1'- and H2'-proton resonances were assigned by means of 2D-NOE spectroscopy. The base- and H1'-proton chemical shifts were studied as a function of temperature. Proton-proton distances are computed in A- and A'-RNA as well as in A-, B- and Z-DNA. A qualitative interpretation of the observed 2D-NOE intensities shows that r( CGCGCG ) adopts a regular A-type double helical conformation under our experimental conditions. The CD- and 31P-NMR experiments described in this paper are in agreement with this structure both under low- and high-salt conditions.